Movimento sindical e fábricas cooperativas : experiências no ABC paulista - Lorente, Raquel Duaibs Aguiar (2009)
This thesis analyzes the incorporation, beginning in the 1990s, of industrial cooperatives by the Sindicato dos Metalúrgicos do ABC (ABC Metalworkers Union) as a strategy for combating unemployment. The union has gone on to support the cooperatives, and is focusing on companies in crisis and bankruptcy. Once these cooperatives are established, labor is no longer salaried, and once they have become members of a cooperative, workers find themselves in an ambiguous category somewhere between workers and owners. By supporting the cooperative workers, the union develops the attitude that it no is no longer limited to representing salaried workers, broadening its sphere of activity. In order to understand the uncertainties and contradictions of the worker cooperatives and union action, two experiences were analyzed: firstly, metalworkers from a company that s going bankruptcy, which has been negotiating for the payment of their salaries and labor rights in court; in this case the proposed metalworkers cooperative was never realized. Secondly, a cooperative already established that has been functioning for more than five years. The undertaking began with the help of the union after the business went into bankruptcy. With the legal and administrative help of the union, the workers were able to organize in order to revive the business through a regime of self-management. In both cases the option of the workers and the unions forming of a cooperative is discussed, outlining the particularities and paradoxes presented by this option.